(3SdWI GdbGVi ai JaQjO GdLRGA GdLfGFi (B: s (3OQGSI ebGQfI (B/ s - (3efUhQ TGjY MSf Gdabjgs; (3CMeO YhV HdGds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3SdWI GdbGVj aj JaQjO GdLRGFj GdLfGFj hSjdI bGfhfjI aGYdI dJaQjO GdYbGH ShGA CcGf YbhHI Ce JOHjQkG GMJQGRjkG(B: (3hjJMOO fWGbgG GdbGfhfj djTed JaQjO GdYbhHI aj EWGQ GdMOhO GdbGfhfjI GdJj hVYgG GdeTQY HGdfXQ Edi XQha GdhGbYI GdELQGejI hTNUjI eQJcHgG hOQLI GdNWhQI GdELQGejI hab fXe bGfhfjI gj(B: (3GdJOQL Gdcej hGdGNJjGQ GdfhYj hJNaja hJTOjO GdYbhHI hEjbGa JfajPgG hJCLjd GdfWb HgG hGdEYaGA efgG HGdEVGaI Edi JaQjO GdJOGHjQ GdGMJQGRjI GdebQQI efgG ddHGdZjf hcPG GdebQQI ddCMOGK(B. (3hJMjW HgG YOO ef GdVhGHW GdJj Jcad SdGeI GdJWHjb GdbVGFj ddYbhHGJ HYV efgG jJYdb HeHOC GdTQYjI GdLfGFjI hHYVgG jJYdb HJaQjO GdYbhHI ShGA GdeJYdbI efgG HGdLQjeI GdeSJeO ef GdQcf GdeGOj hGdeYfhj(B: (3Ch GdeJYdbI HGdLGfj hGdeLfj Ydjg hcPG GdJOGHjQ GdGMJQGRjI GdJj JTed GdLQjeI GdSGHbI hGdNWhQI GdELQGejI GdJj jJYjf Ydi GdbGVj GdLfGFj eQGYGJgG hGdGYJOGO HgG YfO JbOjQ GdLRGA GdLfGFj ShGA CcGf YbhHI Ce JOHjQG GMJQGRjG s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2017s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B726-760s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3JTOjO hJNaja GdYbhHIs; (3JaQjO GdLRGA GdLfGFis; (3fXGe GdYbhHGJ GdHOjdI s; (3JGgjd GdbGVj GdLfGFjs; (3GdJOQL Gdcej ddYbhHI s; (3GdJOQL GdfSHj ddYbhHI s; (3GdXQha GdbVGFjI GdeNaaI s; (3GdXQha GdbVGFjI GdeTOOI s; (3GdGYJjGO Ydi GdGLQGe s; (3GdYbhHI GdaQYjI s; (3GdJOGHjQ GdGMJQGRjI s; (3QO GdGYJHGQ s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs